Revision of ants formerly known as genus pachycondyla (Hymenoptera: Formicidae: Ponerinae) of Sabah - Anati Sawang (2015)
Taxonomic status of the ant genus Pachycondyla Smiths, F. 1858 is the most complex in Ponerine ants. Pachycondyla is heterogeneous and proved to be non-monophyletic genus. As part of Borneo Island, Sabah is an important study site which is facing habitat change that affects ant diversity. Recent study by Schmidt and Shattuck in 2014 rearranged the Pachycondyla into several genera and most of the genera are revived. This study aims at i. revising the taxonomy of ant genus formerly known as Pachycondyla ant in Sabah; ii. studying the distribution of ant genus formerly known as Pachycondyla ants in Sabah; iii. studying the nesting behavior of ants formerly known as genus Pachycondyla ant in Sabah. Revision on formerly known as genus Pachycondyla ants from Sabah was conducted through specimen collection and examinations of specimens from BORNEENSIS, Institute for Tropical Biology and Conservation, Universiti Malaysia Sabah; Insects Collection Centre of Forest Research Centre, Sepilok; Entomological museum, Sabah Parks and Seiki Yamane Collection, Department of Earth and Environmental Sciences and Faculty of Science Kagoshima University. Fresh specimens of ants were collected from several places around Sabah by using colony search method. Six genera of ants formerly known as genus Pachycondyla have been recognized which are Brachyponera, Buniapone, Ectomomyrmex, Euponera, Mesoponera and Pseudoneoponera. A total of 20 species with six new species and three subspecies raised to full species based on morphological characters of worker caste. Five species with a new species are recognized in ant genus Brachyponera: P. flavipes Yamane, 2007, luteipes (Mayr, 1862), obscurans (Walker, 1859), pilidorsalis Yamane, 2007 and villus sp. nov. Ant genus Buniapone is represented only by one species:B. amblyops (Emery, 1887). Five species are recognized in genus Ectomomyrmex with three new species: E. astuta Smith, 1858, E. Keningauensis sp. nov., E. leeuwenhoeki (Forel, 1886), E. magnus sp. nov and E. maliauensis sp. nov. Genus Euponera only represented by one species: E. sharpi (Forel, 1901). Four species are recognized in genus Mesoponera which two are new and one raised to full species: M. kilau sp. nov, M. javana (Forel, 1905) stat. nov., M. rubra Smith, 1857 and M. similerubra sp. nov. Four species of which two are raised to full species are recognized in genus Pseudoneoponera: P. brevior (Forel, 1901) stat. nov., P. debilior (Forel, 1901) stat. nov., P. sandakana (Wheeler, 1919) and P. tridentata Smith, 1958. The distribution of ants formerly known as genus Pachycondyla was high in Danum, Gunung Tambuyukon, Imbak, Keningau, Poring and Maliau Basin where the forests are pristine and under good management. Several rare species such as P. brevior was only recorded in Maliau, P. sandakana from Sandakan, Poring and Danum and P. debilior from Poring, Gunung Tambuyukon and Imbak. Ant formerly known as genus Pachycondyla prefer nesting in dead wood as shown in P. tridentata, P. debilior, M. similerubra and M. rubra. Genus Brachyponera and P. brevior on the other hand prefer building their nest in the soil and leaf litter.